Development of CTL-approached Students Activity Worksheet in Environmental Change Learning Material to Increase Students’ Learning Outcome - Syarifah, Mila Nur; Iswari, Retno Sri (FMIPA UNNES, 2021)
The innovation of student activity worksheet is one of the alternative ways to complement teaching materials in 2013 curriculum. The learning process will be more meaningful if the student activity worksheet used raises contextual material. The purpose of this study is to analyze the feasibility and practicality of CTL-approched student activity worksheet in environmental change material as one of the teaching materials in the learning process. The research method used in this study is a modified Research and Development (RnD) by Sugiyono (2015). The instruments used in this study are validation sheet by material and media experts, student activity worksheet readability questionnaire sheet by students, practicality questionnaire sheet by teacher & students, and interview guidelines. The validity of the material obtains a score of 82.14% with very Feasible criteria and it shows the suitability of the material presented with the CTL approach. The validity of the media obtains a score of 94.6% with very valid criteria and it shows the suitability of the graphic and language aspects. The results of the readability test by students shows a score of 75.2% with Feasible criteria. The result of the practicality assessment of student activity worksheet by teacher reaches a score of 95.83% with very practical criteria and by students reachs a score of 76.23% with practical criteria. Based on the research results, it can be concluded that the developed-CTL-approched student activity worksheet is very feasible and practical to use in learning process.